An Econometric Estimation Of Nigeria’s Export Competitiveness In The Global Market - Eboreime, O. F.; Umoru, David (European Scientific Journal, ESJ, 2016)
In the midst of stiff global competition among industrialized countries focuses on how Nigeria, as a developing economy develop policies and strategies for her exports competitiveness for sustainable development. To achieve this, this paper has estimated Nigeria’s exports competitiveness in the World market by utilizing the Bound Testing approach. The econometric estimate suggest that Nigeria’s exports are less competitive in the United Kingdom but highly competitive in the United States, Japan and Canada. Nigeria’s exports are strongly influenced by the level of foreign income and exchange rate at least for the United States, Japan and Canada. The study thus recommends amongst other things that, the Nigerian government should vis the foreign currencies and further develop and upgrade local industries in order to improve the productivity of these industries for better competition in the global market. The study thus recommends amongst others, that Nigeria should concentrate in the exportation of her goods and services to countries where her products are highly competitive, such as United State, Japan and Canada.